2017
DOI: 10.5505/iuyd.2017.03522
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of The Extended Technology Acceptance Model in Online Travel Products

Abstract: This study integrates perceived enjoyment and perceived trust into a technology acceptance model (TAM) to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
2
12
0
1
Order By: Relevance
“…As expected, perceived ease of use had a significant effect on perceived usefulness. This study's result was consistent with a previous study conducted by Sevim et al [52] and Ha and Stoel [125]. On the other hand, the study's results showed that perceived ease of use did not significantly affect attitude.…”
Section: Discussion: Augmented Reality Adoption and Open Innovationsupporting
confidence: 92%
See 2 more Smart Citations
“…As expected, perceived ease of use had a significant effect on perceived usefulness. This study's result was consistent with a previous study conducted by Sevim et al [52] and Ha and Stoel [125]. On the other hand, the study's results showed that perceived ease of use did not significantly affect attitude.…”
Section: Discussion: Augmented Reality Adoption and Open Innovationsupporting
confidence: 92%
“…Perceived ease of use is considered the degree to which the consumers perceive new services or products as superior to their substitutes [27]. Adopting new technology towards its usefulness depends on the perceived ease of use [52,53]. Ha and Stoel's [53] study results revealed similar findings on online learning system usage intention.…”
Section: Perceived Ease Of Usementioning
confidence: 93%
See 1 more Smart Citation
“…Perceived usefulness and trustworthiness of technology are important determinants of a user's intention to use technology [17]. Perceived usefulness and perceived ease of use were associated with a positive attitude [18], to be the most prominent external factors that influence the use of a technology [19], and use as considerable roles in the adoption of technology [20]. Acceptance of the technology also was affected by many factors: behavioral intention, attitude, perceived usefulness, experience perceived of use and quality factors [21], but the perceived usefulness construct was shown to be the strongest predictor of intention to use technology [22].…”
Section: Acceptance Of Student On Accounting Applicationmentioning
confidence: 99%
“…The user intention to use technology dominantly determines the perceived usefulness and trust of technology [15]. Perceived usefulness plays a considerable role and to be the strongest predictor of user intention to adopt and use technology [16,17]. Technology is accepted by users not only because it is useful but also because it is easy to use [18].…”
Section: B Student Acceptance Of the Applicationsmentioning
confidence: 99%